Transcriptome analysis identification of A-to-I RNA editing in granulosa cells associated with PCOS - Kong, Fan-Sheng; Lu, Zijing; Zhou, Yuan; Lu, Yinghua; Ren, Chun-Yan; Jia, Ruofan; Zeng, Beilei; Huang, Panwang; Wang, Jihong; Ma, Yaping; Chen, Jian-Huan (Frontiers in Endocrinology, 2023)
Background: Polycystic Ovary Syndrome (PCOS) is a complex multifactor disorder in women of reproductive age worldwide. It has been reported that RNA editing may affect the pathological procession of PCOS, but the role of RNA editing in the pathological processes of PCOS remains unclear. Methods: The dataset was obtained from the NCBI Gene Expression Omnibus database, which included five women with PCOS and six women without PCOS (control). A validated dataset that was downloaded from the European Nucleotide Archive Databank was used to validate the credibility of the differential editing events. Transcriptome-wide bioinformatics tools were utilized to analyze adenosine-to-inosine (A-to-I) RNA editing in PCOS and control samples. Results: A total of 17,395 high-confidence A-to-I RNA editing sites were identified in 3,644 genes in all samples. As for differential RNA editing, there were 545 differential editing sites in 259 genes, TUBA1B:chr12:49128795 and MX1:chr21:41452734 were synonymous variant sites, and NUP43:chr6:149725375, RBBP4:chr1:32680141, and PHLDA1:chr12:76027474 were the most significant three 3' untranslated regions (3'UTR) variants. Furthermore, we identified twenty sites that demonstrated a significant correlation between editing levels and gene expression levels. Notably, the expression levels of MIR193b-365a Host Gene (MIR193BHG) and Hook Microtubule Tethering Protein 3 (HOOK3) exhibited significant differences between individuals with PCOS and the control group. Functional enrichment analysis showed that these 259 differential edited genes were related to apoptosis and necroptosis pathways. RNA binding proteins (RBPs) analysis revealed that RNA Binding Motif Protein 45 (RBM45) was predicted as the most frequent RBP binding with RNA editing sites. Additionally, we observed a correlation between seven differential editing sites and the RNA editing enzyme Adenosine Deaminase RNA Specific B1 (ADARB1). Moreover, the validation dataset confirmed the presence of 55 common differential edited genes and nine differential editing sites. Conclusion: Our research sheds light on the potential role of RNA editing in the pathophysiology of PCOS and highlights its epigenetic implications. These findings provide valuable insights that could contribute to the development of more targeted and effective treatment options for PCOS.